Structuring of embodiment design problem based on the product lifecycle. (4th April 2005) - Scaravetti, Dominique; Nadeau, Jean-Pierre; Pailhes, Jerome; Sebastian, Patrick
Early stages of the design process are often based on designers' experience; assumptions and irreversible decisions restricting the solution space are taken. It is difficult to take into account simultaneously every requirement imposed by the different phases of the product life-cycle. In this paper, a method is proposed to perform the analysis of the embodiment design problem. It facilitates the search of the indispensable elements, suitable for structuring the preliminary design phase. Our approach is performed for the relevant life-cycle situations of the product. A four level analysis (need, functions, organic structure and physical behaviours) is proposed. The set of structuring elements allow the design problem definition as a Constraint Satisfaction Problem (CSP).